(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The aim of the research is to define the performance evaluation process, its importance, objectives, and the necessary steps to achieve it. It also aims to define Key Performance Indicators (KPIs) and explain their significance, as well as identify the main obstacles that hinder the implementation of these indicators. Additionally, the research aims to introduce specialized banks and their goals in promoting economic and industrial development. Furthermore, it highlights the impact of performance evaluation through the deployment of KPIs and directing them towards achieving the objectives of specialized banks. The researchers relied on a set of tools that assist in achieving the goals of the current research, including selecting and utilizing certain key performance indicators to effectively evaluate performance in specialized banks and achieve their objectives. The research targeted the community of public banks operating in Iraq, while the research sample included a specialized development bank in the industrial sector. The research reached several conclusions, including a decline in the ratio of profitable assets to total assets over the years under investigation, with the indicator decreasing continuously from 40.09% to 27.84%. The research recommended a number of recommendations, including the necessity for bank management to diagnose the issue of profitable assets and attempt to solve these problems by optimizing the investment of banking assets and utilizing them to increase bank profitability and achieve industrial development.